Biomass‐Derived Carbon for High‐Performance Batteries: From Structure to Properties. (8th April 2022) - Sun, Yu; Shi, Xiao‐Lei; Yang, Yan‐Ling; Suo, Guoquan; Zhang, Li; Lu, Siyu; Chen, Zhi‐Gang
Abstract: Owing to the sustainability, environmental friendliness, and structural diversity of biomass‐derived materials, extensive efforts have been devoted to use them as energy storage materials in high‐energy rechargeable batteries. A timely and comprehensive review from the structures to mechanisms will significantly widen this research field. Here, it starts with the operation mechanism of batteries, and it aims to summarize the latest advances for biomass‐derived carbon to achieve high‐energy battery materials, including activation carbon methods and the structural classification of biomass‐derived carbon materials from zero dimension, one dimension, two dimension, and three dimension. Each strategy starts with carefully selected examples and then moves to illustrate the underlying transport mechanism of electrons in the structure. In the end, challenges, strategies, and outlooks are pointed out for the future development of biomass‐derived carbon materials. Overall, this review will help researchers choose appropriate strategies to design biomass‐derived carbon materials, thereby promoting the application of biomass materials in battery design. Abstract : This review comprehensively summarizes the internal structure of biomass‐derived carbon materials, which aims to provide suitable environment‐friendly and low consumption green materials for high‐performance batteries design.